The Effects of Green Accounting, Carbon Emission Disclosure, and Tax Aggressiveness on Firm Value with Corporate Social Responsibility as a Moderating - Edelin Giska Luthfia; Sofie; Kanitsorn Terdpaopong (Cv. Syntax Corporation Indonesia, 2026)
This study examined the effects of green accounting, carbon emission disclosure, and tax aggressiveness on firm value, with corporate social responsibility (CSR) as a moderating variable and profitability as a control variable. This research reflected the growing global emphasis on sustainability, particularly in the energy sector, where business operations generate substantial environmental impacts. The study focused on oil and gas, coal, and metals and minerals companies listed on the Indonesia Stock Exchange during 2019–2023 due to their direct exposure to natural resource extraction and environmental impacts. This study employed a quantitative approach using secondary data obtained from annual reports and sustainability reports. Purposive sampling resulted in 55 firm-year observations, which were analyzed using panel data regression with the Random Effects Model (REM) through Stata software. The results showed that green accounting had a positive and significant effect on firm value, indicating that environmental accounting practices enhanced investor confidence and corporate reputation. Carbon emission disclosure did not have a significant effect on firm value, suggesting that carbon-related information had not yet become a primary consideration for investors. Tax aggressiveness had a significant effect on firm value, indicating that tax strategies influenced market perceptions when associated with operational efficiency and economic benefits. CSR was found to moderate the relationships between green accounting, carbon emission disclosure, and tax aggressiveness and firm value. These findings provide important implications for decision-makers, investors, and policymakers in developing sustainability strategies and regulations while contributing to the literature on sustainability accounting and corporate finance in Indonesia. Ultimately, the findings emphasize the importance of balancing economic performance, environmental responsibility, tax strategies, and consistent CSR implementation to sustainably enhance firm value.